Looking from the steps of the Manufactures Building toward the Machinery Hall, Alaska-Yukon-Pacific Exposition, Seattle, Washington, 1909 - Nowell, Frank H., 1864-1950 (1909)
Caption on image: X30. Steps of the Manufacturers' Building and Machinery Hall. Publisher: Portland Post Card Co. (no. x30) PH Coll 78.70 See Also: PH Coll 443.40 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number